Empowering the Ranupani Village Community in Realizing the Smart Village - Tiwi Fadilah; Achmad Faesol (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
In 2021, at the Indonesian Tourism Village Award (ADWI), the Ministry of Tourism and Creative Economy named Ranupani Village, Lumajang Regency, as the best village in the homestay category. Ranupani Village fulfills the requirements to be categorized as a smart village. The term smart village is actually part of the universal service obligation (USO) program which functions as a means to carry out digital transformation in three domains, namely economy, society and government. This study intends to see how the community empowerment process is, what are the results and what challenges are faced in the community empowerment process towards a smart village. This study used a descriptive qualitative approach using interview, observation, and documentation data collection techniques. The results of the study show that the development of smart villages goes through three stages of the process. Starting from the first stage, namely preparation, then planning, and ending with socialization. These three stages of the process then produce smart governance and smart economy which at a practical level take the form of Simple Village and IKas (Digital Cashier for UMKM). Because a smart village requires massive digital transformation, the life of the people of Ranupani Village, who are not yet fully familiar with information technology, is transformed into a social challenge in realizing a smart village. These three stages of the process then produce smart governance and smart economy which at a practical level take the form of Simple Village and IKas (Digital Cashier for UMKM). Because a smart village requires massive digital transformation, the life of the people of Ranupani Village, who are not yet fully familiar with information technology, is transformed into a social challenge in realizing a smart village. These three stages of the process then produce smart governance and smart economy which at a practical level take the form of Simple Village and IKas (Digital Cashier for UMKM). Because a smart village requires massive digital transformation, the life of the people of Ranupani Village, who are not yet fully familiar with information technology, is transformed into a social challenge in realizing a smart village.